Pengaruh Game Online Terhadap Perilaku Siswa Kelas V SDN Kota Bengkulu - Efri Rosa; Puspa Djuwita; Hasnawati Hasnawati (Universitas Bengkulu, 2021)
The study aims to determine the effect of online games on the behavior of students in class V SD Negeri Gugus 12 Kota Bengkulu. The research method is survey. The study population is all students of class V SD Negeri Gugus 12 Kota Bengkulu with total sample of 77 students from Class V SD Negeri Gugus 12 Kota Bengkulu taken by using simple random sampling technique. The instrument is a questionnaire with rating scale and likert scale. Data collection techniques uses questionnaires. Technique of data analysis uses simple linear regression analysis. The result of research showed significant level ? = 0,05 significant regression, proved that the value of fcount (32,73) is bigger than ftable (3,97). Thus, the result of the test makes the regression equation expressed with Y = 33,955 + 0,789 can be used to conclude that there is influence of online game to behavior of student in grade V SD Negeri Gugus 12 Kota Bengkulu. Constant of 33.955: means that if the online game value is 0, then the student behavior (Y) positive value is equal to 33.955. Regression coefficient of student behavior variable equal to 0,789: means that if game online increases in score 1, hence student behavior (Y) will increase equal to 0,789. Coefficient is positive means a positive relationship between online game variables (X) and student behavior variables (Y). Increasing online game scores are marked by the lower interest of students towards online games then the better the behavior of students and vice versa.